Navigating the Political Waters of Open Access Publishing in Libraries - Borchert, Carol A.; Simser, Charlene N.; Robertson, Wendy C. (My University, 2016)
In recent years, many libraries have forayed into the world of open access (OA) publishing. While it marks a major shift in the mission of libraries to move from providing access to content to generating and creating content ourselves, it still involves the same basic values regarding access to information. The environment has changed, and libraries are adapting with new approaches and new staff skills to promote these fundamental values. The authors selected nineteen libraries and conducted phone interviews with a specific list of questions, encouraging discussion about how each library approached being a publisher. This chapter examines the politics and issues involved, and makes recommendations for defining our roles in this new territory. The authors highlight the approaches various libraries have taken—and the challenges faced—in selecting a platform, writing a business plan, planning for preservation, educating researchers about OA publishing, working with a university press, marketing, and navigating staff training issues. The chapter concludes with recommendations for areas of focus and future research.